Analisis Berpikir Kritis Matematis Siswa Ditinjau Dari Big Five Personality - Ayang Setiawan; Guntur Maulana Muhammad; Elsa Komala (Jurnal Dimensi Matematika, 2022)
This study aims to describe students' mathematical critical thinking skills with the Big Five personality types, namely Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticism. This research is a descriptive research with a quantitative approach. Data collection technique used in this research is a Big Five personality type questionnaire and a written test. The research subjects consisted of 10 students who were selected from 29 students with purposive sampling technique. Questionnaire analysis data representing personality types were calculated to determine the dominant personality type in students, after that a mathematical critical thinking ability test was carried out on 10 students to be analyzed as data for classifying students' mathematical critical thinking ability levels analyzed using descriptive analysis. The results obtained are as follows: (1)The critical thinking ability of students with the Openness personality type meets the characteristics of high critical thinking abilities. (2)The critical thinking ability of students with Conscientiousness personality type meets the characteristics of a very high critical thinking ability level. (3)The critical thinking ability of students with Extraversion personality type meets the characteristics of a high level of critical thinking ability. (4)The critical thinking ability of students with Agreeableness personality type meets the characteristics of a high level of critical thinking ability. (5)The critical thinking ability of students with the Neuroticism personality type meets the characteristics of a moderate level of critical thinking ability. (6)The type of personality with the characteristics of very high critical thinking skills in learning mathematics is the Conscientiousness personality type